2010
DOI: 10.1104/pp.109.151753
|View full text |Cite
|
Sign up to set email alerts
|

Silencing NaTPI Expression Increases Nectar Germin, Nectarins, and Hydrogen Peroxide Levels and Inhibits Nectar Removal from Plants in Nature

Abstract: Native flower visitors removed less nectar from trypsin proteinase inhibitor (TPI)-silenced Nicotiana attenuata plants (ir-pi) than from wild-type plants in four field seasons of releases, even when the nectar repellant, nicotine, was also silenced. Analysis of floral chemistry revealed no differences in the emission of the floral attractants benzylacetone and benzaldehyde or in the concentrations of nectar sugar and nicotine between wild-type and ir-pi flowers, suggesting that these two lines are equally able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…[13,63] as in our study. Evaluating various Nicotiana taxa, N. rustica had higher nectar protein concentrations, compared to either the other two species involved in our study (Table 1), or to Nicotiana species investigated previously [13,23,63]. The 5 major proteins in the floral nectar of the ornamental tobacco N. langsdorffii × N. sanderae var.…”
Section: Alkaloid Content Of the Floral Nectarmentioning
confidence: 91%
See 1 more Smart Citation
“…[13,63] as in our study. Evaluating various Nicotiana taxa, N. rustica had higher nectar protein concentrations, compared to either the other two species involved in our study (Table 1), or to Nicotiana species investigated previously [13,23,63]. The 5 major proteins in the floral nectar of the ornamental tobacco N. langsdorffii × N. sanderae var.…”
Section: Alkaloid Content Of the Floral Nectarmentioning
confidence: 91%
“…In the nectar of N. attenuata the concentration of nicotine was 3 ± 0.35 µg/mL [13]. The mean concentrations of nicotine measured by us in the nectar of N. alata and N. rustica were within the range of 0.79-2.5 µg/mL which was found to be attractive and even addictive for honeybees [55], whereas nicotine concentrations in N. tabacum nectar slightly exceeded 5 µg/mL, which can already have aversive effect.…”
Section: Alkaloid Content Of the Floral Nectarmentioning
confidence: 99%
“…There is evidence that plant PIs protect specific tissues, act as storage proteins, regulate the activity of proteases, and direct their release (Ryan, 1973;Mosolov and Valueva, 2005). Plants altered in the expression of endogenous PIs display changes in growth rate (Zavala et al, 2004a;Xie et al, 2007), flower morphology and seed development (Sin et al, 2006), phloem structure (Xie et al, 2007), and nectar protein composition (Bezzi et al, 2010). These alterations in fitness-relevant traits showed that members of the potato inhibitor type II family (PI-II), formerly associated with defense, can have other physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Why T. mucorea larvae prefer ir-pi plants in the pith choice tests remains unclear. One explanation could be an altered total protein content as it has been shown for the nectar of ir-pi plants (Bezzi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…attenuata uses a combination of toxins and digestibility reducing defenses, both of which are elicited by herbivore attack. Trypsin protease inhibitors (TPIs) are an effective component of this inducible defensive system that reduces the performance of folivores by targeting their main proteolytic digestive enzymes (van Dam et al, 2000;Glawe et al, 2003;Zavala and Baldwin, 2004;Horn et al, 2005;Zavala et al, 2008;Bezzi et al, 2010). Nicotine, a neurotoxin, generally reduces consumption by a variety of herbivores (Steppuhn et al, 2004).…”
mentioning
confidence: 99%